Spinal Decompression Sickness in an Experienced Scuba Diver: A Case Report and Review of Literature. (October 2019) - Saadi, Altaf; Ferenczi, Emily A.; Reda, Haatem
Decompression sickness from diving is a rare but potentially reversible cause of spinal injury. Early treatment with hyperbaric oxygen is associated with a better neurologic outcome, making prompt recognition and management clinically important. We describe a case of a 65-year-old diver who presented with thoracic back pain and bilateral leg weakness after a 70 feet of sea water (fsw) (21 meters of sea water [msw]) dive, with no acute abnormality on spinal magnetic resonance imaging (MRI). He made a partial recovery after extended hyperbaric oxygen therapy. We discuss the epidemiology and pathophysiology of central nervous system injury in decompression sickness, as well as acute management and prognostic factors for recovery, including the role of adjunctive therapies and the implications of negative MRI. Ultimately, clinicians should make the diagnosis of spinal cord decompression sickness based primarily on clinical evaluation, not on MRI findings.